Indigenous West Nile Virus Infections in Horses in Albania. (November 2013) - Berxholi, K.; Ziegler, U.; Rexhepi, A.; Schmidt, K.; Mertens, M.; Korro, K.; Cuko, A.; Angenvoort, J.; Groschup, M. H.
Summary: Serum samples collected from 167 equines of 12 districts in Albania were tested for West Nile virus–specific antibodies by enzyme‐linked immunosorbent assay and virus neutralization assay, using WNV lineage 1 and 2. In addition, 95 bird serum samples from Albania and 29 horse samples from Kosovo were tested in ELISA. An overall seroprevalence rate of 22% was found in horses from Albania, whereas no specific antibodies were found in the equine samples from Kosovo and the bird samples. This is the first report indicating WNV infections in animals in Albania, and the first reported seroprevalence study conducted for Kosovo. These results provide evidence for widespread infections of WNV in Albania.